PERAN AIESEC LOCAL COMMITTEE (LC) BANDUNG DALAM MENDUKUNG PENCAPAIAN SUSTAINABLE DEVELOPMENT GOALS (SDGS) - Claudia Karina Putri (Universitas Komputer Indonesia, 2018)
As an International Non-Governmental Organization, AIESEC Bandung is supporting the achievement of SDGs. There are various activities of AIESEC Bandung, both internship programs and social projects that have an impact on achieving SDGs. In addition, AIESEC Bandung has carried out internships and social projects long before the SDGs were issued. After the SDGs were issued, AIESEC Bandung then included SDGs goals and targets relevant to the AIESEC Bandung social project. Based on the results of interviews and literature studies, it can be seen that there are various social projects in AIESEC Bandung that help achieve SDGs, such as the Sampurasun, I Green, Social Entrepreneur, Impacting, Malala and I Care for Disabled projects. Both project participants and project partners feel the positive results of these social projects. The activities of AIESEC Bandung which continue to take place every year also make this activity sustainable. Even so, there are still many improvements that must be improved by AIESEC Bandung to support the achievement of SDGs, such as social project sustainability issues, difficulties in finding partners and the absence of cooperation with the government.